2014
DOI: 10.1111/jam.12311
|View full text |Cite
|
Sign up to set email alerts
|

Fungal endophytes enhance wheat heat and drought tolerance in terms of grain yield and second-generation seed viability

Abstract: Aims: We evaluated the impact of fungal endophyte symbiosis on the growth, ecophysiological and reproductive success of wheat exposed to heat and drought. Methods and Results: The resistance of pot-grown wheat to heat or drought stress was measured by quantifying efficiency of photosystem II (F v /F m ), plant height, average seed weight (ASW), total seed weight (TSW), water-use efficiency (WUE) as well as time to 50% germination and percentage germination of second-generation seeds produced under heat stress,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(87 citation statements)
references
References 42 publications
1
82
0
3
Order By: Relevance
“…The strong dominance of some fungal groups (Table 4) indicates that they can play a relevant role in plant physiology. Fungal species can produce a wide variety of growth regulators, such as gibberellins (GAs), abscisic acid (ABA), and auxins (IAA) (You et al, 2012), and they can also confer tolerance to adverse biotic and abiotic factors (Hubbard et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The strong dominance of some fungal groups (Table 4) indicates that they can play a relevant role in plant physiology. Fungal species can produce a wide variety of growth regulators, such as gibberellins (GAs), abscisic acid (ABA), and auxins (IAA) (You et al, 2012), and they can also confer tolerance to adverse biotic and abiotic factors (Hubbard et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, an extreme example is Cypripedium (Lady slippers) terrestrial orchids, which seeds obligately depending on mutualistic endophytic fungi for germination (Vujanovic et al 2000). By moderating the physiological stress response via mycovitality Hubbard et al 2012), the endophytic fungi improve wheat seed germination stages under drought and heat, yielding wheat plants with significantly improved agricultural traits (Hubbard et al 2014b).…”
Section: The Mycodependency Spectrum: From Mycotrophy To Mycovitalitymentioning
confidence: 99%
“…Hubbard et al (2014b) demonstrated that mycovitality improves wheat's seed germination (Baskin and Baskin 2014), overall host productivity, and resilience against drought and heat. Further studies have shown that these advantages are transmitted to the offspring, thus potentially bringing about a plant epigenetic modification (Hubbard et al 2014a).…”
Section: Mycovitality: Improving Dormancy Release and Germinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have reported the discovery of microbial symbionts from wild and crop plants. Several of these symbionts show positive effects on crop productivity and stress tolerance of tomato, wheat, rice, barley, and other crops mainly under green house conditions [40][41][42][43]. Microbial symbionts can increase plant productivity and stress tolerance via various mechanisms.…”
Section: Introductionmentioning
confidence: 99%